THE IMPACT OF TRANSFORMATIONAL LEADERSHIP AND TEACHER’S PEDAGOGICAL COMPETENCE ON EDUCATIONAL QUALITY: A QUANTITATIVE STUDY IN INDONESIAN PRIMARY SCHOOL - Emmelia Maria Sulistyorini; Maryanto; Ghufron Abdullah (SOSIOEDUKASI, 2025)
his study examines the impact of transformational leadership and teachers' pedagogical competence on the quality of education in public elementary schools in East Ungaran District. Using a quantitative approach with a causal survey design, the research explores how these variables influence educational quality. Data was collected from 148 teachers across 14 schools, with instruments measuring transformational leadership, pedagogical competence, and educational quality. The findings reveal that transformational leadership significantly influences educational quality, as school principals with a clear vision, motivation, and exemplary behavior create a productive and innovative school environment. Additionally, teachers' pedagogical competence, which includes effective teaching strategies and understanding student needs, plays a vital role in improving educational outcomes. The study shows that both variables combined explain 61.7% of the variation in educational quality. The synergy between transformational leadership and pedagogical competence creates a positive and sustainable learning environment, contributing to enhanced teacher performance and quality learning. The study offers practical recommendations for school leaders and policymakers to focus on developing leadership skills and enhancing teacher competence through continuous professional development, as these factors significantly contribute to improving the quality of education in primary schools.